Identifying the Most Autonomy-Supportive Message Frame in Digital Health Communication: A 2x2 Between-Subjects Experiment - Smit, Eline Suzanne; Zeidler, Chamoetal; Resnicow, Ken; de Vries, Hein (Journal of medical Internet research, 2019)
The effectiveness of digital health communication may be increased by enhancing autonomy supportiveness. This study aimed to identify the most autonomy-supportive message frame within an intervention for increasing vegetable intake by testing the effect of the following 2 strategies: (1) using autonomy-supportive language and (2) providing choice. A Web-based 2 (autonomy-supportive vs controlling language)×2 (choice vs no choice) experiment was conducted among 526 participants, recruited via a research panel. The main outcome measures were perceived autonomy support (measured using the Virtual Care Climate Questionnaire, answered with scores 1 to 5), perceived relevance (measured with one question, answered with scores 1 to 5), and overall evaluation of the intervention (measured with 1 open-ended question, answered with scores 1 to 10). Choice had a significant positive effect on the overall evaluation of the intervention (b=.12; P=.003), whereas for participants with a high need for autonomy, there was a significant positive effect on perceived relevance (b=.13; P=.02). The positive effect of choice on perceived autonomy support approached significance (b=.07; P=.07). No significant effects on any of the three outcomes were observed for language. Results suggest that provision of choice rather than the use of autonomy-supportive language can be an easy-to-implement strategy to increase the effectiveness of digital forms of health communication, especially for people with a high need for autonomy.